Is there a co-operative advantage? Experimental evidence on the economic and non-economic determinants of demand. Issue 2 (December 2016) - Altman, Morris
Highlights: Using Canadian data (Saskatchewan), I conduct a survey experiment examining the importance of non-economic factors as determining the demand for products sold by consumer co-operatives. I provide a theoretical framework for examining the hypothesis that non-economic factors should not affect the demand for products sold by consumer co-operatives. I find, based on my sample population, that when co-operatives charge the same product price controlling for quality both co-op members and those who are not members have a strong preference for products sold by consumer co-operatives. I also find that, even as the price of co-op products increase relative to that sold by non-coops, demand does not collapse, contrary to what's predicted by conventional economics. The evidence suggests that non-economic variables matter importantly in determining demand and that consumers increase their wellbeing when they purchase co-operative products. Abstract: Focusing on consumer co-operatives, I test the conventional economic worldview that relative price is a main determinants of consumer behaviour using survey instruments in a classroom setting. I examine the role which non-economic variables such as 'warm glow' might play in determining demand. My findings challenge the narrow economic worldview that only economic variables count; but support a core assumption that economic variables are of fundamental importance to individual's choice decisions. Significantly, individuals are willing to pay higher prices for co-operative products even if they are not co-op members. However, as the price of co-operative products increases relative to the products of non-co-operatives, demand falls amongst both non-members and members of co-operatives. But demand is more inelastic for co-op members. When price is the same for co-ops and non-co-op, even non-co-ops members prefer to purchase products sold by co-operatives. The co-operative advantage provides co-ops with a protective belt against competition from non-cooperatives. This also speaks to the potential strength of consumer co-ops in competitive markets. Firms that invest in both economic and non-economic determinants of consumer demand, should be characterized by a significant competitive advantage.